INTEGRASI NILAI-NILAI TASAWUF DALAM IBADAH, MOTIVASI, DAN PROFESIONALISME DI LINGKUNGAN KERJA MODERN - Adang Kadarusman; Basan Sanjaya; Sukemi; Ahmad Parasdi; Sobirin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
In today’s era, marked by intense work pressure and materialistic orientation, the need to strike a balance between professional responsibilities and spiritual well-being is increasingly evident. Sufism, as the spiritual dimension of Islam, offers a holistic framework for developing a work ethic rooted in sincere worship, intrinsic motivation, and ethical professionalism. This study aims to explore how Sufi principles such as sincerity (ikhlas), patience (sabr), asceticism (zuhud), and mindfulness (muraqabah) can be practically integrated into the professional work environment. Utilizing a qualitative descriptive approach based on literature review, this research finds that applying Sufi values helps foster integrity, responsibility, and visionary character in employees. A case study conducted at the Permata Keadilan Law Office in South Tangerang illustrates the positive impact of Sufi-based spiritual practices on work enthusiasm, employee loyalty, and service quality. Keywords: Sufism, Worship, Motivation, Professionalism, Islamic Work Ethics